Mémoire indienne dans The Swinging Bridge de Ramabai Espinet : la construction d’une identité indo-trinidadienne diasporique - Rodolphe Solbiac (Études Caribéennes)
This work proposes to read The Swinging Bridge as a process by which a hybrid Indo-Trinidadian Diaspora is created. It argues that the novel’s recovery of memory constitutes a process by which individual memories turn into a collective diasporic memory which re-establishes links between Indo-Trinidadians dispersed in Canada and Trinidad. We demonstrate that rebinding to the Trinidadian space and recovering part of the memory of the Indian historical centre set the three spaces in a diasporic relation.This study also demonstrates that the novel’s narrative semantics rejects cultural conflict, as well as essentialism and creates a hybrid cultural identity. It establishes that the construction of diaspora at work in The Swinging Bridge advocates for the appreciation routes rather than roots and is compatible with the idea of a multi-locational diasporic consciousness.